Kayu Kelapa Sebagai Bahan Alternatif Untuk Mebel di Area Public Rumah Tinggal - Sarah Phebryanti (Intra, 2015)
The introduction of the characteristics possessed by coconut wood before further processing into a furniture for home stay is very important. Some coconut wood shortage that must be addressed is the coconut wood has a moisture content that is quite large, easily attacked by fungi or insects, prone to rupture and easily weathered fibers when exposed to water. Not only that, the selection of the proper construction and finishing are also factors that determine the quality of a furniture. Based on these characteristics, several steps were necessary to improve the quality of coconut wood. The home stay is where most of the community to spend time. In residences needed comfort and safety in use and take advantage of a furniture. The size and amount of furniture that aan placed in a chamber that is determined by the amount of space. That will be a discussion of the types of research that houses, furniture standard sizes for these types of homes, furniture formation as what is appropriate to the character of coconut wood, construction can be applied, until the appropriate finishing that can be used. While finishing the most appropriate is to use polyurethane, while not suitable for melamine melamine can close the wood fiber.